2018
DOI: 10.1371/journal.pone.0200740
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac function index derived from femoral and jugular indicator injection for transpulmonary thermodilution with the PiCCO-device: A prospective observational study

Abstract: IntroductionCardiac function index (CFI) is a trans-pulmonary thermodilution (TPTD)-derived estimate of systolic function. CFI is defined as the ratio of cardiac output divided by global end-diastolic volume GEDV (CFI = CO/GEDV). Several studies demonstrated that the use of femoral venous access results in a marked overestimation of GEDV, while CFI is underestimated. One study suggested a correction formula for femoral venous access that markedly reduced the bias for GEDVI. Therefore, the last PiCCO-algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Multivariate analyses revealed a significant independent correlation between increased GEDVI, EVLWI, and the femoral injection site [6]. Due to this and further evidence suggesting relevant differences caused by the site of indicator injection [5], we performed measurements of both sites (jugular/femoral) in patients with jugular and femoral access in routine clinical practice and interpreted the results in a clinical context.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Multivariate analyses revealed a significant independent correlation between increased GEDVI, EVLWI, and the femoral injection site [6]. Due to this and further evidence suggesting relevant differences caused by the site of indicator injection [5], we performed measurements of both sites (jugular/femoral) in patients with jugular and femoral access in routine clinical practice and interpreted the results in a clinical context.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have already shown that TPTD-derived parameters with femoral indicator injections have led to a significant overestimation of the GEDVI compared to jugular indicator injections [5]. Concerning the injection site and investigating TPTD in patients undergoing vv-ECMO therapy, Herner et al not only illustrated how all TPTD-derived parameters changed after the initiation of vv-ECMO therapy, but they also noted that the parameters measured in patients after femoral injections were significantly higher than those after jugular injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of the PiCCO system is its needs of transpulmonary measurement and its invasive nature. Recent studies have shown that when more distant central lines are used, the device is not able to predict the cardiac function reliably (27). Despite its limitations, PiCCO is extremely effective in goal directed therapy of patients in ICU and early fluid resuscitation efforts, thereby, decreasing mortality (28).…”
Section: Piccomentioning
confidence: 99%
“…These systems can provide information on the hemodynamic status of critically ill patients and can also be used in the perioperative setting. Although abovementioned devices have made it possible to improve the treatment of critically ill patients and optimize goal-directed therapy, they are expensive, not commonly available, and have shown limitations in providing reliable data in different contexts [ 3 5 ].…”
mentioning
confidence: 99%